Monetary and Career based Motives at the Core of EFL Programs: Problems and Solutions - Fallas Escobar, Christian; Ennser-Kananen, Johanna; Bigelow, Martha (GIST – Education and Learning Research Journal, 2016)
In this paper, we discuss the dominant discourses that use monetary and careerbased reasons to justify the learning and teaching of English in Costa Rica by drawing parallels to similar phenomena taking place in Japan, Korea, Canada, and Colombia. We argue that the propagation of these discourses has resulted in the commodification of EFL teaching and learning in Costa Rica, as programs are designed to meet narrow material-based interests and purposes. The reflection includes an analysis of publicity around EFL learning, a national initiative to improve EFL teaching/learning, a specific EFL program in a public Costa Rican university, and the opinions of students from this program. We demonstrate how the construction of English as the means by which professionalism, economic growth, and wealth can be accomplished has shaped EFL curricula in particular ways, thereby neglecting diverse motivations for EFL learning. We finish the paper by advocating for the creation of more democratic spaces in EFL classrooms where both teachers and learners can critique in constructive ways the impact that these dominant discourses have on themselves as individuals and on EFL curricular at large.